The view from Castle Rock : stories - Munro, Alice, 1931- (Knopf : Distributed by Random House, 2006)
A collection of stories about the Laidlaw family starting in the wilds of the Scottish Borders, their voyage to Canada, to stories set in Alice (Laidlaw) Munro's present time.